ANALISIS PENGARUH HARMONIOUS PASSION DAN OBSESSIVE PASSION TERHADAP EMPLOYEE JOB PERFORMANCE (Studi Pada Karyawan PT. X Tangerang) - Rayhandika Rahman Fawwaz; Andriyani Andriyani (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to analyze the effect of harmonious passion and obsessive passion on employee job performance. This study consists of two independent variables and one dependent variable. The independent variables in this study are harmonious passion and obsessive passion. The dependent variable in this study is employee job performance. The sample was selected using the purposive sampling method. Data were collected by sending an online questionnaire to the employees of PT. X Tangerang. A total of 78 employees with ≥ 1 year tenure have participated in this study. The data were analyzed by using multiple linear regression analysis with SPSS 25 for Windows program. The results of this study indicate that harmonious passion has a significantly positive effect on employee job performance. Meanwhile, obsessive passion has no significant effect on employee job performance.